Impact of COVID-19, lockdowns and vaccination on immune responses in a HIV cohort in the Netherlands - Otten, Twan; Jiang, Xun; Gupta, Manoj Kumar; Vadaq, Nadira; Cleophas-Jacobs, Maartje; dos Santos, Jéssica C.; Groenendijk, Albert; Vos, Wilhelm; van Eekeren, Louise E.; Blaauw, Marc J. T.; Meeder, Elise M.G.; Richel, Olivier; et al. (Frontiers in Immunology, 2024)
During the COVID-19 pandemic, major events with immune-modulating effects at populationlevel included COVID-19 infection, lockdowns, and mass vaccinations campaigns. As immune responses influence many immune-mediated diseases, population scale immunological changes may have broad consequences. We investigated the impact of lockdowns, COVID-19 infection and vaccinations on immune responses in the 2000HIV study including 1895 asymptomatic virally-suppressed people living with HIV recruited between October 2019 and October 2021. Their inflammatory profile was assessed by targeted plasma proteomics, immune responsiveness by cytokine production capacity of circulating immune cells, and epigenetic profile by genome-wide DNA methylation of immune cells. Past mild COVID-19 infection had limited long-term immune effects. In contrast, COVID-19 vaccines and especially lockdowns significantly altered both the epigenetic profile in immune cells at DNA methylation level and immune responses. Lockdowns resulted in a strong overall exaggerated immune responsiveness, while COVID-19 vaccines moderately dampened immune responses. Lockdown-associated immune responsiveness alterations were confirmed in 30 healthy volunteers from the 200FG cohort that, like the 2000HIV study, is part of the Human Functional Genomics Project. Our data suggest that lockdowns have unforeseen immunological effects. Furthermore, COVID-19 vaccines have immunological effects beyond anti-SARS-CoV-2 activity, and studies of their impact on non-COVID-19 immune-mediated pathology are warranted.